2014
DOI: 10.1371/journal.pone.0100508
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey on Dietary Supplements Consumption among Italian Teen-Agers

Abstract: IntroductionIn the last decades, dietary supplements consumption has increased in the Western world for all age groups. The long-term potentially dangerous effects related to an indiscriminate consumption of dietary supplements are still unknown and are becoming a matter of public health concern. Therefore, the aims of the present study were: to explore the contribution of dietary supplements to micronutrient daily intake, and to evaluate awareness and knowledge about dietary supplements.MethodsParticipants (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 20 publications
7
32
0
1
Order By: Relevance
“…In the present study, a nationwide survey of dietary supplement use in elementary, junior high, and high school students was conducted. The prevalence of current and previous dietary supplement use in overall school-aged children across Japan was 21.6% (current use, 16.4%; previous use, 5.2%), which was lower than for those of the same age in the United States (31–46.2%) [ 16 , 17 ], Italy (34.8%) [ 18 ], and Korea (34%) [ 19 ], but consistent with the results from Australia (20.1–23.5%) [ 20 ] and an urban Japanese city of Nara prefecture study (20.4%) [ 21 ]. Not only was the prevalence of dietary supplement use in each grade similar, but the increase in use in line with increasing age as shown in the Nara study was also replicated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a nationwide survey of dietary supplement use in elementary, junior high, and high school students was conducted. The prevalence of current and previous dietary supplement use in overall school-aged children across Japan was 21.6% (current use, 16.4%; previous use, 5.2%), which was lower than for those of the same age in the United States (31–46.2%) [ 16 , 17 ], Italy (34.8%) [ 18 ], and Korea (34%) [ 19 ], but consistent with the results from Australia (20.1–23.5%) [ 20 ] and an urban Japanese city of Nara prefecture study (20.4%) [ 21 ]. Not only was the prevalence of dietary supplement use in each grade similar, but the increase in use in line with increasing age as shown in the Nara study was also replicated.…”
Section: Discussionmentioning
confidence: 99%
“…The global market of DS is a multibillion-dollar commerce, with the Asia Pacific being the second largest market accounting for 31% of the total market share [ 6 ]. Studies established that there are substantial national variations regarding the prevalence of dietary supplement consumption in children and adolescents; 20% in Australia [ 7 ], 32% to 37% in the United States [ 8 , 9 ], 35% in Italy [ 10 ], 20% to 22% in Japan [ 11 , 12 ] and 33% in South Korea [ 13 ]. Specifically, the prevalence of vitamin/mineral supplements (54%) and food supplements (40%) intakes are more pronounced among Malaysian adolescents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have documented the use of supplements and their associated determinants among adolescents and young adults. Most studies over the past 10 years have been conducted in the United States [ 8 , 9 ], Europe [ 10 , 20 , 21 , 22 ] and Australia [ 7 ] with limited studies conducted in the Asian countries [ 12 , 13 , 14 , 23 ]. However, the external reliability of most questionnaires utilized in earlier studies has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrolled use of supplements in the general population may represent a health risk as there is increasing evidence that high intakes of some dietary supplements, such as vitamin E or vitamin A, may be more harmful than beneficial (3)(4)(5) . One common finding among studies on supplement use in Europe is that the major motives for supplement use are related to health (6)(7)(8)(9)(10) . Furthermore, it has been reported that supplement use is more frequent in women than in men (1,11,12) , in older people than in younger people (1,12) and in people with higher levels of education compared with those with lower levels of education (13,14) .…”
mentioning
confidence: 99%